The Joint Universality for L-Functions of Elliptic Curves - Garbaliauskienė, V. (Nonlinear Analysis: Modelling and Control, 2004)
A joint universality theorem in the Voronin sense for L-functions of elliptic curves over the field of rational numbers is proved.